1998
DOI: 10.1007/s001250050930
|View full text |Cite
|
Sign up to set email alerts
|

Soluble vascular cell adhesion molecule-1 and E-selectin levels in relation to vascular risk factors and to E-selectin genotype in the first degree relatives of NIDDM patients and in NIDDM patients

Abstract: The first degree relatives of non-insulin-dependent diabetes mellitus (NIDDM) patients are at increased risk of coronary artery disease and also have a lifetime risk of NIDDM of up to 40 % [1]. The development of these conditions appears to be predicted by the presence of features of insulin resistance and associated clustering of atherosclerotic risk in these subjects [2].Adhesion molecules are expressed on the cellular surface of endothelium in response to inflammatory stimuli [3] and can also be detected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
48
2
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 31 publications
(42 reference statements)
7
48
2
1
Order By: Relevance
“…Although we did find a moderately strong association between sVCAM-1 and CRP levels, we showed that the association between sVCAM-1 levels and risk of cardiovascular mortality was independent of CRP levels, suggesting that sVCAM-1 levels increase cardiovascular risk through a pathway different from that of an acute phase response. Third, increased levels of sVCAM-1 could reflect generalized endothelial d y s f u n c t i o n , since we and others showed high sVCAM-1 levels to be associated with high vWF levels (18,22,31) and the presence of microalbuminuria (18), i.e., potential markers of generalized endothelial dysfunction (42)(43)(44). However, we showed sVCAM-1 levels to be associated with the risk of cardiovascular mortality independent of vWF levels and of microalbuminuria, which argues against the idea of increased sVCAM-1 levels being a marker of generalized endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Although we did find a moderately strong association between sVCAM-1 and CRP levels, we showed that the association between sVCAM-1 levels and risk of cardiovascular mortality was independent of CRP levels, suggesting that sVCAM-1 levels increase cardiovascular risk through a pathway different from that of an acute phase response. Third, increased levels of sVCAM-1 could reflect generalized endothelial d y s f u n c t i o n , since we and others showed high sVCAM-1 levels to be associated with high vWF levels (18,22,31) and the presence of microalbuminuria (18), i.e., potential markers of generalized endothelial dysfunction (42)(43)(44). However, we showed sVCAM-1 levels to be associated with the risk of cardiovascular mortality independent of vWF levels and of microalbuminuria, which argues against the idea of increased sVCAM-1 levels being a marker of generalized endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 86%
“…Most (20,(25)(26)(27)(28)(29), but not all (30,31), studies have shown sVCAM-1 levels to be increased among type 2 diabetic subjects as compared with nondiabetic subjects, and sVCAM-1 levels have been shown to be independently associated with carotid artery intima-media thickness in type 2 diabetes patients (29). In view of these considerations, we investigated the association of sVCAM-1 concentration and risk of cardiovascular and all-cause mortality among nondiabetic and type 2 diabetic subjects in a prospective, populationbased cohort study.…”
mentioning
confidence: 99%
“…Moreover, an association of E-selectin concentrations with HbA 1 c values in patients with Type I diabetes [4,5] and with Type II diabetes [8] has been found. However, other recent studies could not detect a relation between AM concentrations and glycaemic control [9,24]. These conflicting results could be explained by differences in the degree of glycaemic control between these different study cohorts [4,24].…”
Section: Discussionmentioning
confidence: 88%
“…However, other recent studies could not detect a relation between AM concentrations and glycaemic control [9,24]. These conflicting results could be explained by differences in the degree of glycaemic control between these different study cohorts [4,24]. The influence of the glycaemic control on plasma AM concentrations is further suggested by results showing that the association between HbA 1 c and E-selectin disappeared after improvement of glycaemic control [8].…”
Section: Discussionmentioning
confidence: 96%
“…In particular, there was no effect of the 561A4C polymorphism in contrast to a weak association reported in UK patients with type 2 diabetes mellitus. 46 This may be a population or disease-specific association.…”
Section: Discussionmentioning
confidence: 99%